Pengaruh Persepsi Pendidikan terhadap Minat Siswa Kelas 12 SMA Muhammadiyah 1 Taman dalam Melanjutkan Pendidikan Ke Perguruan Tinggi - Cahyati, Eci; Musfiroh, Lailatul; Putri, Noviana Ramadhani; Pangestu, Jesti Argi Yuan; Ananta, Imelia Tsabitah; Wulandari, Ayu (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the effect of analyzing students' perceptions on their interest in continuing their education at a higher level, which was conducted at XII level students of SMA Muhammadiyah1 Taman. This study is expected to reveal the extent to which students' perceptions of the importance of education affect their interest in continuing their education at the college level. Using a quantitative approach, the research utilized questionnaires as the data collection method. The test results show that there is a significant influence between students' perceptions of education on their interest in continuing their education at the tertiary level, with a significance value below 0.05. This shows that variable X (student perceptions) has an effect on variable Y (interest in continuing education).